Internal friction vs. thermal shock in C/C composites. (1st December 2016) - Liu, Yue; Fu, Qiangang; Zhao, Fengling; Sun, Guodong; Li, Hejun
Abstract: In order to understand thermal fatigue behavior of carbon/carbon (C/C) composites, they were subjected to thermal cycles between 1373 K and room temperature for different times. Their microstructure, mechanical strength and internal friction after thermal cycles were studied. The results show that the flexural strength of C/C composites increased from 69 MPa to 89 MPa after 10 thermal cycles between 1373 K and room temperature, and internal friction increased significantly with the increase of thermal cycles. The improvement of the internal friction and the strength were attributed to the increase of the residual thermal stresses at the interfaces. Further increase in the thermal cycles will reduce the interfacial strength between carbon matrix and fibers due to matrix cracking and the decrease of interfacial bonding strength.